The Vibrio cholerae SpeG Spermidine/Spermine N-Acetyltransferase Allosteric Loop and β6-β7 Structural Elements Are Critical for Kinetic Activity - Le, Van Thi Bich; Tsimbalyuk, Sofiya; Lim, Ee Qi; Solis, Allan; Gawat, Darwin; Boeck, Paloma; Lim, Ee Qing; Renolo, Rosselini; Forwood, Jade K.; Kuhn, Misty L. (Frontiers in Molecular Biosciences, 2021)
Polyamines regulate many important biological processes including gene expression, intracellular signaling, and biofilm formation. Their intracellular concentrations are tightly regulated by polyamine transport systems and biosynthetic and catabolic pathways. Spermidine/spermine N-acetyltransferases (SSATs) are catabolic enzymes that acetylate polyamines and are critical for maintaining intracellular polyamine homeostasis. These enzymes belong to the Gcn5-related N-acetyltransferase (GNAT) superfamily and adopt a highly conserved fold found across all kingdoms of life. SpeG is a SSAT protein found in a variety of bacteria, including the human pathogen Vibrio cholerae. This protein adopts a dodecameric structure and contains an allosteric site, making it unique compared to other SSATs. Currently, we have a limited understanding of the critical structural components of this protein that are required for its allosteric behavior. Therefore, we explored the importance of two key regions of the SpeG protein on its kinetic activity. To achieve this, we created various constructs of the V. cholerae SpeG protein, including point mutations, deletions, and chimeras with residues from the structurally distinct and non-allosteric human SSAT protein. We measured enzyme kinetic activity toward spermine for ten constructs and crystallized six of them. Ultimately, we identified specific portions of the allosteric loop and the β6-β7 structural elements that were critical for enzyme kinetic activity. These results provide a framework for further study of the structure/function relationship of SpeG enzymes from other organisms and clues toward the structural evolution of members of the GNAT family across domains of life.